Effects of different thermal pretreatments on the biodegradability and bioaccessibility of sewage sludge. (1st July 2019) - Zhang, Yucheng; Xu, Suyun; Cui, Minghao; Wong, Jonathan W.C.
Graphical abstract: Highlights: Thermal alkaline pretreatment promoted methane yield of sludge. Protein-like organics mainly located in SPOM and REOM fractions. Biodegradability is well correlated with the ratio of IRB to IPB . Bioaccessibility of readily degradable organic matters was enhanced by LAT. Abstract: Thermal hydrolysis has proven to be a successful approach to make sewage sludge more amenable to anaerobic digestion. Three heat pretreatment scenarios were compared in this study, i.e. thermal alkaline treatment (LAT, 0.1 M NaOH, 80 °C), low temperature thermal treatment (LT, 80 °C) and high temperature thermal treatment (HT, 170 °C). The biodegradability of pretreated sludge was testified by using biochemical methane potential (BMP) test, meanwhile, the repartition and complexities of organic matters in sludge subjected to various pretreatments were characterized by a revised chemical extraction protocol combined with 3D fluorescence spectroscopy. The cumulative methane yield of sewage sludge was significantly increased by LAT (+135%), LT (+95%) and HT (+112%) as compared to the control. Nevertheless, results show that the solubilization degree of sludge was insignificantly correlated to BMP values, meanwhile high correlation values were observed for the soluble polysaccharide concentration in hydrolysate. The degradation rates of bioaccessible fraction of soluble particulate organic matter (SPOM) and readily extractible organic matter (REOM) were improved after thermal pretreatments at varied levels, which indicates that the chemical accessibility is positively correlated with the bioaccessibility. Furthermore, the biodegradable index F digestion was proposed to evaluate the biodegradability of organic matter, which is helpful for the optimization of various pretreatment strategies.